Legal Aid Advocacy for the Poor in Law of Welfare States - Ismi, Hayatul (The Indonesian Journal of International Clinical Legal Education, 2019)
Indonesia is a lawful welfare state, which means that the governmenthas a duty and responsibility in realizing the social justice and thegeneral welfare of the people. Paragraph (1) of the 1945 Constitution,stated that The State must ensure the implementation of equality in thestanding before the law. Nowadays it seems only the lower class thatmust obey the law, while the upper class seems to be immune to thelaw. They are hiding from the law behind the layers of their ownmoney. As if the law can be sold using money, even for those whocommit major crimes, corruption for example. While the lowerclasses who commit minor crimes can be imprisoned. Our country is acountry of law, then the law should be enforced, for all people and notjust for Reviews those who have the money. To realize theimplementation of the idea of a lawful welfare state then the Stateshould guarantee the right of every person to reach justice. In otherwords, the State must guarantee the implementation of legal aid to theimpoverished or Reviews those who cannot afford so that nonehas no access to justice that is mandated by the constitution. Legal aidadvocacy for the impoverished in the concept of a lawful welfare stateis certainly to be important in realizing the ideals of the lawful welfarestate that achieve social justice and general welfare of thepeople. Therefore, it is important to know the concept of advocacysuitable for the impoverished in a welfare state.